Decision-Making under Persistent Uncertainty. A New Paradigm of Decision-Making and its Multiple Explanatory Capacities - Zamfir, Cătălin (Calitatea Vieții, 2008)
This paper was presented in the Conference of the European Sociological Association, Glasgow, 2007. These are conclusions drawn from the authors’ research carried out during several decennia. The following topics are discussed: types of uncertainty in decision making, the relationship between objective uncertainty and subjective uncertainty, procedures of decision making under persistent uncertainty and the way the decision makers face problems like adopting a good enough decision, absorb uncertainty at an acceptable level and achieve a reasonable level of consensus.